Imagined Futures Hope, Risk and Uncertainty - Cook, Julia (Critical Studies in Risk and Uncertainty,, 2018)
This book presents the findings of a recent interview-based study of how 28 young adults living in Melbourne, Australia viewed and related to both the personal and societal future. In so doing it addresses issues such as how individuals imagine the future of their society, and whether this has any bearing on the way in which they perceive and relate to their own, personal future. The respondents' future imaginings are also considered in relation to influential theoretical accounts that have sought to diagnose the character of contemporary society, and with it the future horizon. Drawing on this discussion, some alternative ways of conceptualising micro experiences of future-oriented thinking are proposed, and the role that hope can play in this process is addressed. This book will appeal to readers who are interested in the sociology of risk and uncertainty, time, and youth. .